Doctoral Studies: A Comparative Analysis between European and National (Greek) Level - Skondra, Katerina; Kavasakalis, Aggelos (Advances in Social Sciences Research Journal, 2025)
The present paper investigates the evolution of Doctoral Studies by comparing the European and the national level (Greece). The research question is “How Doctoral Studies have been evolved at Europe and Greece during the 21st century”? The investigation is conducted via the analysis of policy texts and the production of “codes”. The time frame is set at the three decades of the 21st century. At the European level, the research focuses on the supranational entity of the European Union (EU) and the Bologna Process (ΕΗΕΑ). Moreover, it analyzes the official discourse of key stakeholders, such as the European University Association (EUA) and the European Students’ Union (ESU). At the national level, it draws on relevant legislation and a prior research’s findings. After analyzing and producing codes related to developments in Doctoral Studies at the European and the national level, a comparative analysis highlights the convergences and divergences between the two levels.